Onabotulinum toxin-A versus extended release tolterodine in the management of idiopathic overactive bladder in children: A pilot randomised controlled trial (OVERT trial). Issue 1 (February 2021) - Brown, Michaela; Williamson, Paula R.; Sutton, Laura; Melling, Charlotte; Lewis, Malcolm; Webb, Nicholas J.A.; Goyal, Anju
Summary: Background: Idiopathic Overactive Bladder is the most common cause of urinary incontinence in children. Anticholinergic medications are successful in only 20% of those with daily wetting so there is a real need to find a more effective treatment for this condition. Onabotulinum toxin A injections are often used as a treatment but there have been no randomised controlled trials investigating effectiveness in children. Objective: To provide information that would inform the design and conduct of a definitive trial comparing onabotulinum toxin A with extended-release tolterodine for the management of therapy resistant idiopathic overactive bladder in children. Specific objectives were to assess rates of eligibility, recruitment, acceptability of randomisation, loss to follow-up, acceptability of urodynamic assessment and obtain primary outcome data for sample size estimation. Study design: Single-centre, parallel, two-arm, open-label pilot randomised controlled trial. Eligible patients (aged 7–16 years) were recruited at Royal Manchester Children's Hospital and randomised (1:1) using a web-based system. Trial registration: EudraCT 2014-001068-36; Funding: UK NIHR Research for Patient Benefit Programme. Results: 98 patients were assessed for eligibility, 85 (87%) were eligible for screening, parents of 62 (73%) provided consent, 46 (74%) remained eligible and were randomised (onabotulinum = 22, tolterodine = 24). All participants commenced allocated treatment. Two patients withdrew from follow-up. All participants underwent urodynamic assessment at baseline and 35 (76%) additionally at week 6. The mean (standard deviation) number of wetting episodes per day at week 6 was 1.4 (1.7) in the onabotulinum group and 1.6 (1.0) in the tolterodine group. There was one serious adverse event (probably related to the drug) and 22 non-serious adverse events reported by 8 participants in the onabotulinum group (36%). There were 23 non-serious adverse events reported by 9 participants in the tolterodine group (38%). Discussion: Recruitment was challenging but eligibility and consent rates were high as were retention rates. Treatment compliance in the botox group was high but it was difficult to measure in the tolterodine group. Treatment switching was also an issue. Conclusions: Recruitment to a definitive trial was demonstrated to be feasible if a large number of centres are involved, though further consideration is required regarding trial design. Summary figure CONSORT flow diagram. Summary figure